Recombination and its impact on the genome of the haplodiploid parasitoid wasp Nasonia. - Oliver Niehuis; Joshua D Gibson; Michael S Rosenberg; Bart A Pannebakker; Tosca Koevoets; Andrea K Judson; Christopher A Desjardins; Kathleen Kennedy; David Duggan; Leo W Beukeboom; Louis van de Zande; David M Shuker; et al. (PLoS ONE)
Homologous meiotic recombination occurs in most sexually reproducing organisms, yet its evolutionary advantages are elusive. Previous research explored recombination in the honeybee, a eusocial hymenopteran with an exceptionally high genome-wide recombination rate. A comparable study in a non-social member of the Hymenoptera that would disentangle the impact of sociality from Hymenoptera-specific features such as haplodiploidy on the evolution of the high genome-wide recombination rate in social Hymenoptera is missing. Utilizing single-nucleotide polymorphisms (SNPs) between two Nasonia parasitoid wasp genomes, we developed a SNP genotyping microarray to infer a high-density linkage map for Nasonia. The map comprises 1,255 markers with an average distance of 0.3 cM. The mapped markers enabled us to arrange 265 scaffolds of the Nasonia genome assembly 1.0 on the linkage map, representing 63.6% of the assembled N. vitripennis genome. We estimated a genome-wide recombination rate of 1.4-1.5 cM/Mb for Nasonia, which is less than one tenth of the rate reported for the honeybee. The local recombination rate in Nasonia is positively correlated with the distance to the center of the linkage groups, GC content, and the proportion of simple repeats. In contrast to the honeybee genome, gene density in the parasitoid wasp genome is positively associated with the recombination rate; regions of low recombination are characterized by fewer genes with larger introns and by a greater distance between genes. Finally, we found that genes in regions of the genome with a low recombination frequency tend to have a higher ratio of non-synonymous to synonymous substitutions, likely due to the accumulation of slightly deleterious non-synonymous substitutions. These findings are consistent with the hypothesis that recombination reduces interference between linked sites and thereby facilitates adaptive evolution and the purging of deleterious mutations. Our results imply that the genomes of haplodiploid and of diploid higher eukaryotes do not differ systematically in their recombination rates and associated parameters.